Analysis of teachers' emotions toward their approaches to teching in secondary education by using principal component analysis and cluster analysis - Azamudin, Noor Ain (2013)
The purpose of this study is to investigate the relationship between teachers’ emotions in teaching and their approaches to teaching in secondary education. The study was conducted among 112 teachers in secondary school by using two different questionnaires which are the Approach to Teaching Inventory and the Emotions in Teaching Inventory. The results suggest that there are significant relationship between teachers’ emotions in teaching and the approaches that they used in teaching and learning process either student-focused approaches or teacher-focused approaches. The data was analyse using Principal Component Analysis and cluster analysis. As a result, we identified that teachers experienced more positive emotions when they used student-focused teaching approaches and more negative emotions when they used teacher-focused teaching approaches.